DYNAMIC CHANGES IN CARDIOVASCULAR RISK BIOMARKERS AND CYTOKINES OF MYOCARDITIS-FREE PATIENTS WITH DECOMPENSATED HEART FAILURE AND ISCHEMIC SYSTOLIC DYSFUNCTION - O. N. Ogurkova; E. V. Kruchinkina; A. M. Gusakova; T. E. Suslova; V. V. Ryabov (Медицинская иммунология, 2021)
The development and progression of heart failure is associated with a variety of pathophysiological mechanisms, of particular interest is the study of the inflammatory response as a fundamental link in the pathogenesis of CHF and its main component – decompensation. An open, non-randomized, prospective study was carried out to evaluate the clinical and morphological features of subclinical inflammation in patients with acute decompensation of ischemic chronic heart failure with a reduced ejection fraction. The study included 25 patients with decompensated ischemic CHF with left ventricular ejection fraction < 40% aged 35 to 75 years (60.12±9.3 y. o.). In this study the dynamics of the serum content of C-reactive protein (CRP), N-terminal fragment of the brain natriuretic peptide precursor protein (NT-proBNP), soluble ST2(sST2), insulin-like growth factor-1 receptor (IGF-1R), interleukin-6 (IL-6), interleukin-10 (IL-10), tumor necrosis factor-α (TNFα) was performed by multiplex immunoassay using the FLEXMAP 3D. All studied patients were divided into two groups depending on the diagnosed myocarditis: patients with no signs of myocarditis and patients with myocarditis. It was found that in the group of patients with diagnosed myocarditis there was an increased content of CRP, IGF-1R, IL-6 and IL-10, TNFα compared to the group of patients without myocarditis. The median concentrations of the NT-proBNP and sST2 in both groups did not differ. At the follow-up visit a year later, there was a decrease in the content of CRP, NT-proBNP, IL-6 in both groups. In the group of patients with myocarditis, an increase in the content of sST2, IGF-1R, IL-10 was observed. Thus, the study carried out in dynamics revealed significant differences in the degree of changes in the serum activity of pro- and anti-inflammatory cytokines and biomarkers of cardiovascular risk in patients with decompensated heart failure with systolic dysfunction with diagnosed myocarditis and in its absence.